Bacteriocins and its applications: mini-review - Cubillo-Komarovova, Plamen (2024)
Bacteriocins are molecules with antibacterial activity, which makes them important tools for human use. Currently, these molecules show promise for food preservation without chemical additives and for the clinical treatment of bacterial infections. Some favorable characteristics of bacteriocins are their synergy with other bacteria and their activity against biofilms. Biotechnological strategies such as the activation of biosynthetic groups of genes, induction by genetic engineering or co-cultures, and incorporation in bioprocesses, can make the use of these molecules in different industries increasingly closer. The objective of this mini literature review is to offer recent and updated information on the applications of bacteriocins in the fields of health, agronomy and industry, from a biotechnological perspective.